Solidification and stabilization of bottom ash in concrete as fine aggregate replacement - Nor Haslinda, Mohamad Zainudin (2014)
Fine aggregate is a one of main ingredient that uses to produce concrete. Large amount of fine aggregate that used in industry increase the construction cost. This research was conducted to determine the effect of coal bottom ash toward compressive strength of concrete. The experimental was carried out by using coal bottom ash as sand replacement in the concrete mix grade30 with ratio 0%, 10%, 20%,,30%, 40% and 50%. The compressive strength of the concrete by using 100mm x 100mm x 100mm cube size is determined at 7,28 and 60 days age of curing. The result show the compressive strength of control concrete is high compare to the coal bottom ash concrete. The concrete compressive strength was decrease when the coal bottom ash replacement up to 20% was mix in concrete cube. The strength of concrete will increase when the concrete was immersion in the water curing with long duration time. The increment of strength for 20% coal bottom ash as a sand replacement was increase after 28days compare to other percentages. Meanwhile, the water retention time was measured after 28days curing age for iweek in the water immersion with ratio 1/10. This research also aims to study the performance of concrete containing bottom ash toward leaching characteristic and to investigate the influence of the solidification or stabilization of heavy metal materials. The leaching test for the concrete mix is measured for 1 hour, 1 day, I week and 1 month in the water immersion with ratio 1/10. The result from leaching test by using ICP-MS Agilent 7500 test method shown the heavy metal that contain in the concrete was acceptable for environment. So the concrete with coal bottom ash replacement can use in the construction in the Malaysia.